2016
DOI: 10.1002/jor.23449
|View full text |Cite
|
Sign up to set email alerts
|

Osteocyte physiology and response to fluid shear stress are impaired following exposure to cobalt and chromium: Implications for bone health following joint replacement

Abstract: The effects of metal ion exposure on osteocytes, the most abundant cell type in bone and responsible for coordinating bone remodeling, remain unclear. However, several studies have previously shown that exposure to cobalt (Co2+) and chromium (Cr3+), at concentrations equivalent to those found clinically, affect osteoblast and osteoclast survival and function. In this study, we tested the hypothesis that metal ions would similarly impair the normal physiology of osteocytes. The survival, dendritic morphology, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…These small molecules may transfer mechanical loading-induced signals via connexins, resulting in connexin upregulation, increased osteogenesis, and increased osteocyte differentiation [20]. Another possible mechanism via which fluid shear stress inhibits osteocyte apoptosis is that fluid flow may accelerate oxygen and nutrient supply to the osteocytes, increasing cell viability [21].…”
Section: Discussionmentioning
confidence: 99%
“…These small molecules may transfer mechanical loading-induced signals via connexins, resulting in connexin upregulation, increased osteogenesis, and increased osteocyte differentiation [20]. Another possible mechanism via which fluid shear stress inhibits osteocyte apoptosis is that fluid flow may accelerate oxygen and nutrient supply to the osteocytes, increasing cell viability [21].…”
Section: Discussionmentioning
confidence: 99%
“…Cr 3+ ions, however, did not influence the gene expression and therefore most likely interact with the mineralization process directly. Shah et al showed comparable effects of cobalt and chromium on the mineralization of murine “osteoblast to osteocyte-like” cell line MLO-A5 [ 37 ]. The inhibition of mineralization by soluble Cr 3+ or on soluble CrPO 4 might be due to the binding of phosphate to Cr 3+ , thereby reducing the availability of the ionic form [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that the gene expression in the Wnt/β‐catenin signaling pathway of MLO‐Y4 cells (e.g., Wnt3a and β‐catenin) was up‐regulated under the FSS stimulation (Santos et al, ; Huang et al, ). However, the gene expression of DKK1 (a critical negative regulator of the Wnt/β‐catenin pathway) of MLO‐Y4 cells was unaltered after FSS stimulation (Shah et al, ), although numerous in vivo studies have demonstrated that DKK1 expression of osteocytes was significantly suppressed under mechanical loading (Lara‐Castillo et al, ; Pflanz et al, ). It should be noted that most previous studies only investigated the expression of these cytokines of osteocytes in the gene level, and there is a lack of systematic study quantifying the expression of these cytokines in the protein level.…”
Section: Introductionmentioning
confidence: 99%